Direct and Indirect Evaluation Strategies for Course Outcome (CO)-Program Outcome (PO) Attainment of Engineering Physics Course - Archana Sharma (Journal of Research in Education and Pedagogy, 2025)
The constant pursuit of bettering goods, services, or procedures is known as continuous improvement. These initiatives may aim for “incremental” advancement over time or simultaneous “breakthrough” progress. This study examines the evaluation of course exit surveys used to rate first-year undergraduate engineering students at K J Somaiya College of Engineering, one of the higher educational institutions in Mumbai. Students’ perceptions of teaching and learning, their knowledge and abilities linked to Program Outcomes (POs), their assessments of the contributions of their lecturers, their views on academic resources and overall academic performance were all covered in the course exit survey for the subject of Engineering Physics. Prospective institute graduates’ questionnaires have been found to be one of the most useful tools for evaluating the program curriculum’s strengths and weaknesses. The effectiveness of the engineering physics course on the students of the first year B. Tech is determined by student input on their performance and satisfaction. The study was conducted for academic year 2023-24 syllabus structure, for different branches of first year students. The course exit survey is floated among the students in every semester. Outcome-based education strategies have been validated when the entire curriculum aligns with the program outcomes. According to the survey, roughly 70% of participants concur that the curriculum for the Physics is appropriate and helps in enhancing their life-long learning. The objective is to evaluate the effectiveness of the course, identify areas for improvement, and understand students’ perspectives on various aspects of the curriculum, teaching methods, and overall learning experience. The survey covers topics such as course content, teaching quality, assessment methods, and resources provided. The feedback collected is analyzed to provide actionable insights for enhancing the course structure and delivery.